Acute Cardiogenic Shock Induced by Infusional 5-Fluorouracil. (28th October 2014) - Sulpher, Jeffrey; Dattilo, Franco; Dent, Susan; Turek, Michele; Reaume, M. Neil; Johnson, Christopher
Abstract : A 49-year-old patient with metastatic carcinoma of the bladder and no prior history of heart disease presented with diffuse ST elevation, elevated troponins, and biventricular dysfunction requiring intensive care unit admission and inotropic support after receiving her first course of infusional 5-fluorouracil (5-FU). Over the course of several days, the patient's cardiac function and clinical status returned to baseline. A follow-up echocardiogram performed 5 days after initial presentation revealed an ejection fraction of 59 percent, with no evidence of wall motion abnormalities. Subsequent 5-FU chemotherapy was discontinued, and the patient went on to receive second-line chemotherapy.